2017
DOI: 10.1590/1234-56781806-94790550303
|View full text |Cite
|
Sign up to set email alerts
|

Factors that May Lead on the Non-renewal of Certified Organic Product According to Organic Producers in Brazil

Abstract: Abstract:The regulatory process of the organic sector in Brazil began in 1999 and has gone through several changes, culminating in the Decree-Law of December 2007, which established rules for the production and trading of organic products in Brazil. In such Decree, the certification has become a compulsory requirement for production and trading of such products, whose rules governing their obtaining follow rigorous controls standards. As the certification process of organic products is recent and there is a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A study by Scalco et al, (2017) found that organic producers' permanence in certifi ed activities is uncertain if they have diffi culties in meeting the requirement of organic farming. They recommend improving the capacities of service providers such as extension agents to assist and guide organic producers to meet the requirement of organic farming.…”
Section: Complying With Os In Cot Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Scalco et al, (2017) found that organic producers' permanence in certifi ed activities is uncertain if they have diffi culties in meeting the requirement of organic farming. They recommend improving the capacities of service providers such as extension agents to assist and guide organic producers to meet the requirement of organic farming.…”
Section: Complying With Os In Cot Productionmentioning
confidence: 99%
“…Hence, if farmers are unaware of maintaining biodiversity as a fundamental requirement in an organic farm, they may not make an extra eff ort to maintain it. Scalco et al, (2017) mentioned that, if farmers lack information about the requirements in organic production, including biodiversity management, it will be a challenge for them to comply with those requirements. Therefore, though farmers are compliant in some areas, proper investigation is necessary to recognize whether those compliances are intentional or unintentional to take necessary actions to make the compliance sustainable.…”
Section: Moderate Compliancesmentioning
confidence: 99%